Los juegos didácticos y su incidencia en el desarrollo cognitivo de los niños y niñas del primer grado de educación general básica de la escuela San Antonio de Padua de la ciudad de Quito. Periodo lectivo 2013-2014 lineamentos alternativos - Galarza Medina, Cemira Georgina (2014)
This research was part of an analytical, descriptive and explanatory study about "THE EDUCATIONAL GAMES AND ITS IMPACT ON COGNITIVE DEVELOPMENT BASIC GENERAL EDUCATION FIRST-DEGREE CHILDREN” SAN ANTONIO DE PADUA” SCHOOL QUITO CITY. LECTIVO PERIOD 2013-2014 "ALTERNATIVE GUIDELINES, the same that was developed in accordance with the Rules of Academic Board of the National University of Loja. The general objective was formulated: To determine the incidence of Educational Basic General Education First Degree Children Cognitive Development. The Scientific, Analytical-Synthetic, Inductive-Deductive, Model Description and Statistical methods were used. The techniques and instruments used were: Survey applied to Basic General Education First Degree Teachers of "San Antonio de Padua" school of Quito. Period 2013-2014 ", to identify using Educational Games in the daily work with children; and Cognitive Skills Test applied to Basic General Education first degree Children to assess the Cognitive Development.. Analyzed the results of the survey concluded that teachers 50% of the teachers surveyed Educational Games does use in daily work with children and 50% no, To substantiate the research work Cognitive Test was applied to assess the cognitive development with the following results: 73% children have Very Satisfactory Cognitive Development and 27% have unsatisfactory cognitive development.